The effect of aqueous extract of Prunus dulcis on tibial bone healing in the rabbit - Nima Anaraki; Amir Hossein Beyraghi; Abbas Raisi; Farshid Davoodi; Ghasem Farjanikish; Amin Bigham Sadegh (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Bone fractures are medical emergencies that require prompt intervention to help return bone to its normal function. Various methods and treatments have been utilized to increase the speed and efficiency of bone repair. This study aimed to investigate the treatment effects of Prunus dulcis aqueous extract on tibial bone healing in rabbits. Methods All animals were distributed in five groups with six rats in each group, including the sham group, the control group in which tibial lesion was made and received distilled water, treatment groups with 150 mg kg−1, 300 mg kg−1 doses of Prunus dulcis extract, and osteocare treated group. Biochemical blood factors including calcium, phosphorus, and alkaline phosphatase (on days 0, 10, 30, and 50), biomarkers of oxidative stress such as GPx, CAT, and MDA (on days 10 and 30), radiological evaluation, histopathological parameters, and osteocalcin immunohistochemical expression were assessed. Results The data showed calcium levels in the treatment groups increased significantly from day 10 to day 50, respectively, and blood phosphorus levels decreased from day 10 to day 50 in the treatment groups. Alkaline phosphatase initially increased and then decreased in treatment groups. In the treatment groups, GPx and CAT levels significantly increased, and the serum amount of MDA reduced. The best antioxidant results were related to the extract-treated group with a higher dose. Radiographic score was significantly higher in the treatment groups than the control group on day 30. Based on the pathological findings, the healing occurred faster in the extract-treated group with a higher dose. Osteocalcin expression was significantly higher in the control group than that in the treatment groups. Conclusions Treatment with Prunus dulcis extract with a dosage of 300 mg/kg accelerated tibial bone healing in rabbits. Graphical abstract